Provision of public goods, voting and agglomerative bias - Andreas Kopp (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1998)
Skill-biased technical change is identified as the driving force behind the changing skill composition in OECD countries rather than structural change. The finding is partly the result of the sectoral view taken. This paper suggests a different view which uses the production process as a starting point. The economy is divided into physica production, personal services, and intermediate services; these branches are again subdivided. Applying the resulting grid to German data from the Socio-economic Panel shows that a structural change in the production process is driving the skill composition of the German labor force.
Keywords: E24; J21; 330; Lokales öffentliches Gut; Abwanderung und Widerspruch; Ökonomische Theorie der Demokratie; Räumliche Gleichgewichtstheorie; Klubtheorie; Agglomerationseffekt; Theorie